Formation of Monolithic Ion-Selective Transport Media Based on “Click” Cross-Linked Hyperbranched Polyglycerol - Abrahamsson, Tobias; Poxson, David J.; Gabrielsson, Erik O.; Sandberg, Mats; Simon, Daniel T.; Berggren, Magnus (Frontiers in Chemistry, 2019)
In the emerging field of organic bioelectronics, conducting polymers and ion-selective membranes are commonly combined to form device structures represented by resistors, diodes and transistors, and systems thereof, that transport and process both electronic and ionic signals. Such bioelectronics device concepts have been explored in electrophoretic delivery devices that translate electronic addressing signals into the transport and dispensing of small-sized charged biomolecules, such as neurotransmitters, at high specificity and spatiotemporal resolution. Traditional manufacturing approaches of these “iontronic” devices includes classical thin film processing of polyelectrolyte layers and insulators followed by the application of electrolytes and physiological media. This approach makes miniaturization and integration difficult, simply because the ion selective membranes swells after completing device manufacturing. To advance organic bioelectronics and iontronics technology and to reach applications where relatively larger molecules can be delivered, it is important to develop a versatile material system in which the selectivity, with respect to charge and size, can be easily tailormade at the same time enabling easy manufacturing of complex and miniaturized structures. Here, we report a one-pot synthesis approach with minimal amount of organic solvent to achieve cationic hyperbranched polyglycerol films for iontronics applications. The hyperbranched structure allows for tunable pre multi-functionalization, which combines available unsaturated groups used in crosslinking along with ionic groups for electrolytic properties, to achieve a one-step process when applied in devices for monolithic membrane gel formation with selective electrophoretic transport of molecules.